2021
DOI: 10.18510/hssr.2021.956
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of residential housing choices, quality, and affordability in Calabar Metropolis, Southern Nigeria

Abstract: Purpose of the study: This paper examined the housing quality, its affordability as well as the housing choices which residents of Calabar can make. Housing needs in the city continue to rise in response to rapid urbanization rates and thus lead to high housing demands. Methodology: About 384 questionnaires were distributed randomly within six purposively delineated housing districts in Calabar with a 78 percent success rate. The stratification covered all the housing types, from the low to medium and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Housing constitutes among other things, a basic need of man (Chionuma, 2002;Jiboye, 2009). While many authors had defined housing from varying perspectives, Okon and Ikelegu (2021) summed its totality as denoting a measure of, just as it impacts, the standard of households' health, productivity and personal wellbeing. The source further spelt out its influence on national economies as huge, thereby directing financial markets and impacting national growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Housing constitutes among other things, a basic need of man (Chionuma, 2002;Jiboye, 2009). While many authors had defined housing from varying perspectives, Okon and Ikelegu (2021) summed its totality as denoting a measure of, just as it impacts, the standard of households' health, productivity and personal wellbeing. The source further spelt out its influence on national economies as huge, thereby directing financial markets and impacting national growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Okon and Ikelegu (2021), the current state of appalling housing conditions and expenses is a reality that cannot be disregarded. According to their definition, an inexpensive home is one whose price does not necessarily impair one's capacity to satisfy other basic requirements like food, clothes, and medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Akinluyi, Awe, Adeleye, Oso and Taiwo (2022) submitted that cost is concerned with all categories of expenditure associated with the production of a house. Okon et al (2021) came to the conclusion that it would probably be difficult for low-income people to afford homes. Nwanekezie and Okeahialam, (2019) concluded that the main reasons why people in Uyo metropolitan prefer to live in subpar neighborhoods are poverty and unemployment.…”
Section: Introductionmentioning
confidence: 99%